Actuality and projection of the scholastic tradition: philosophy, justice and economics - Gómez Díez, Francisco Javier; Cendejas Bueno, José Luis; Prieto López, Leopoldo J. (Anales del Seminario de Historia de la Filosofía, 2022)
The article presents a set of articles on the present and projection of the scholastic tradition. The starting point is the anthropological turn that, within scholasticism and at the beginning of the fourteenth century, privileged the study of ethics, law and politics and, consequently, the forced development of a moral theology concerned with the human coexistence. The second scholasticism, prolonging this tradition throughout the 16th and 17th centuries, could not remain oblivious to the implications of the profound changes that were taking place: the Discovery of America, the Protestant Reformation, the development of a commercial proto-capitalism and the strengthening of the monarchies. As the Reformation was consolidated in a good part of the European territories, intellectual borders were raised between the various confessions. However - and this is the focus of the papers presented - these borders were porous and, despite the climate of confrontation, various indirect communication channels managed to maintain a single intellectual republic.
Keywords: scholasticism; scholastic philosophy; Francisco Suárez; Francisco de Vitoria; legal thought of scholasticism; economic thought of scholasticism